Seroprevalence and risk factors of Hepatitis E Virus infection among pregnant women in Addis Ababa, Ethiopia - Abebe, Meseret (PLoS One, 2017)
BACKGROUND: Hepatitis E virus (HEV) is highly endemic in several African countries with high mortality rate among pregnant women. The prevalence of antibodies to HEV in Ethiopian pregnant women is not known. The study was conducted to investigate the prevalence of anti-HEV IgG and anti-HEV IgM among pregnant women. MATERIAL AND METHODS: A total of 386 serum samples were collected from pregnant women between April 2014 to January 2015 in Gandhi Memorial Hospital and four selected Health centers in Addis Ababa, Ethiopia. Data were collected for socio demographic characteristics using a structured questionnaire. Serum samples were examined for anti-HEV IgG and anti- HEV IgM using ELISA. The association of anti-HEV status with risk factors was assessed. Factors demonstrating significant association in bivariate analysis were included in multivariate logistic regression models. Analyses were performed using SPSS version 21. RESULTS: Anti- HEV IgG antibody was detected in 122 (31.6%) women and two women (0.5%) were positive for anti-HEV IgM from the total 386 women. Age and educational status had statistically significant association with HEV infection. There was no significant association between anti-HEV antibody seroprevalence rate with trimester, parity, HIV status and other risk factors. CONCLUSION: In this study we found a high seroprevalence rate of anti-HEV IgG among pregnant women in Addis Ababa Ethiopia. Preventive measures like improvement of education and creating awareness may reduce the risk in pregnant women. Moreover nationwide surveillance of HEV especially in rural setting should be conducted to establish a national estimate and validate our findings.